1997
DOI: 10.1029/97gl03165
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of the episode 54 eruption at Kilauea Volcano, Hawaii, from GOES‐9 satellite data

Abstract: Abstract. The free availability of GOES satellite data every 15 minutes makes these data an attractive tool for studying short-term changes on cloud-free volcanoes in the Pacific basin. We use cloud,free GOES-9 data to investigate the chronology of the january 1997, episode 54 eruption of Kilauea Volcano, Hawaii. Seventy-six images for this effusive eruption were collected over a 60-hour period and show the opening •and shutdown of active fissures, the draining and refilling of the Pu'u 'O'o lava lake, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Following the technique of Harris et al (1997aHarris et al ( , 1997b and Harris and Thornber (1999 ) we use volcanic radiance (R2volc), this being the channel 2 radiance of an anomalous pixel minus that of its immediate, non-anomalous background. Following Harris and Thornber (1999 ) we then sum R2volc for all anomalous pixels to give SR2volc.…”
Section: T Echniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the technique of Harris et al (1997aHarris et al ( , 1997b and Harris and Thornber (1999 ) we use volcanic radiance (R2volc), this being the channel 2 radiance of an anomalous pixel minus that of its immediate, non-anomalous background. Following Harris and Thornber (1999 ) we then sum R2volc for all anomalous pixels to give SR2volc.…”
Section: T Echniquesmentioning
confidence: 99%
“…Previously GOES data have been utilised to detect, track and analyse rapidly developing volcanic features such as dispersing volcanic ash plumes (Sawada 1987, Glaze et al 1989, Holasek and Self 1995, and to detect and monitor biomass burning (Menzel et al 1991, Prins andMenzel 1992 ). Until Harris et al (1997a) showed how GOES data could be used to produce a detailed chronology of an eVusive eruption, however, the potential of GOES for volcanic hot spot monitoring remained unexplored in the published literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are posted on the Internet (http://goes.higp.hawaii.edu) usually within 15 min of initial image acquisition. The GOES-based system has provided valuable insights into the development of lava flow-fields and eruption timings at Kilauea Volcano in Hawaii (Harris, Keszthelyi, et al, 1997;Harris & Thornber, 1999) and Fernandina Volcano in the Galapagos Islands (Mouginis-Mark, Snell, & Ellisor, 2000). It has also been used to elucidate processes governing the behaviour of potentially explosive silicic lava domes at Popocatépetl, Mexico (Wright, de la Cruz-Reyna, Flynn, Harris, & Gomez-Palacios, in press) and Lascar .…”
Section: Introductionmentioning
confidence: 99%
“…Since 1998, an automated system at the Hawai'i Institute of Geophysics and Planetology, has been operational, with the task of processing GOES data for monitoring global volcanic activity, and since this time various studies have also confirmed the utility of GOES for determining volcanic activity chronologies (e.g. 47,48). SEVERI, the instrument onboard the most recent Meteosat with infrared imaging capabilities, has similarly been used for such purposes and indeed, has formed part of an automated volcano monitoring system, HOTSAT, which is implemented, along with higher resolution MODIS data, for rapid activity detection and monitoring 49, 50. In 1986, NASA announced its plans for the development of an Earth Observation System (EOS) 51 that would acquire low-Earth orbit observations.…”
Section: Historical Perspective On Sensors Used For Volcanic Observationmentioning
confidence: 99%